The research of the causal relationship between unemployment and emigration in Lithuania - Dudzeviciute, Gitana; Čekanauskas, Justinas (Business: Theory and Practice, 2014)
This paper aims to investigate the causal relationship between unemployment and emigration in Lithuania using Granger – causality test. The research is based on annual data spanning the period of 2004–2012. The investigation encompasses two steps. Firstly, the authors have analyzed the Lithuanian position regarding relationship between unemployment rate and emigration in the context of the European Union countries; secondly, the causality between unemployment and emigration has been determined in the case of Lithuania. On the basis of the European Union countries statistical data, results of the research have revealed a weak correlation between unemployment rate and emigration. On the contrary, evidence has suggested the existence of a strong relationship between unemployment and emigration in Lithuania. Results of the Granger – causality test have showed that unemployment impacts on emigration in Lithuania.